Dampak Manajemen Kepemimpinan Guru dalam Menerapkan Pendekatan Pembelajaran Mendalam terhadap Hasil Belajar Siswa SMK - Mediatrix Tu'baran; A. Grummy Wailanduw; Luthfiyah Nurlaela; I Gusti Putu Asto Buditjahjanto; Rommy Mochamad Ramdhani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Teacher leadership management in Vocational High Schools (SMK) is an important element in creating a learning atmosphere that supports the immersive learning approach, which is believed to improve student learning outcomes. This study aims to explore the influence of teacher leadership management in the implementation of the immersive learning approach on student learning achievement in SMK through a Systematic Literature Review. The method used is in accordance with the PRISMA 2020 guidelines. The results of the study indicate that the type of teacher leadership (instructional, transformational, and teaching) does not have a direct impact, but has an indirect impact on student learning outcomes through three main pathways: (1) improving teacher abilities and professionalism, (2) strengthening students' psychological aspects (such as self-confidence and resilience in learning), and (3) support from the social context and immersive learning strategies. The conclusion of this study confirms that teacher leadership management functions as a driver in building a learning ecosystem that supports the implementation of immersive learning, which ultimately contributes to improving SMK student learning outcomes, both academically and practically.